PERAN BRAND IMAGE DALAM MEMEDIASI PENGARUH GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN (Studi pada produk fashion merek Uniqlo di Denpasar) - Nandaika, M Ega; Respati, Ni Nyoman Rsi (E-Jurnal Manajemen, 2021)
Purchasing decision is an activity that directly determines the product to be purchased based on the value or value of some products. Green marketing is one way to increase product value while maintaining environmental sustainability. The purpose of this research is to find out how the role of brand image in mediating the influence of green marketing on purchasing decisions (Study on Uniqlo brand fashion products in Denpasar). This research was conducted at Uniqlo company. The sample used in this study amounted to 100 respondents using purposive sampling method. Analysis techniques used are path analysis. The results of this study showed that green marketing variables have a positive and significant effect on brand image and purchasing decisions on Uniqlo brand fashion products in Denpasar, brand image has a positive and significant effect on purchasing decisions on Uniqlo brand fashion products in Denpasar, Green marketing can influence purchasing decisions on Uniqlo brand fashion products in Denpasar partially through brand image mediation. In terms of brand image, Uniqlo fashion products must maintain consistency and improve sustainability program. Keywords : Green marketing, brand image, purchasing decisions.